2020
DOI: 10.1007/s00330-020-07256-z
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of prostate cancer on active surveillance: stratification by MRI using the PRECISE recommendations in a UK cohort

Abstract: Objectives The PRECISE recommendations for magnetic resonance imaging (MRI) in patients on active surveillance (AS) for prostate cancer (PCa) include repeated measurement of each lesion, and attribution of a PRECISE radiological progression score for the likelihood of clinically significant change over time. We aimed to compare the PRECISE score with clinical progression in patients who are managed using an MRI-led AS protocol. Methods A total of 553 patients on AS for low- and intermediate-risk PCa (up to G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 29 publications
0
29
0
1
Order By: Relevance
“…mpMRI is an important tool for biopsy planning and also for prostate cancer detection [4,31]. Furthermore, in the future, mpMRI might play an important role for patients under active surveillance [32]. However, an increase in demand for an examination does not automatically lead to an increase in supply, due to the restricted availability of MRI scanners and comparably long examination times using standard techniques.…”
Section: Discussionmentioning
confidence: 99%
“…mpMRI is an important tool for biopsy planning and also for prostate cancer detection [4,31]. Furthermore, in the future, mpMRI might play an important role for patients under active surveillance [32]. However, an increase in demand for an examination does not automatically lead to an increase in supply, due to the restricted availability of MRI scanners and comparably long examination times using standard techniques.…”
Section: Discussionmentioning
confidence: 99%
“…The PRECISE scoring system was developed in 2017 [16] in order to standardise reporting of serial MRI scans in patients on AS to detect clinically significant radiological changes sufficient to either trigger additional investigations or switch to immediate radical treatment. Since then, several groups [17][18][19][20][21] have demonstrated a high negative predictive value of PRECISE, suggesting that it can be used to avoid routine repeat biopsy if the disease is regarded as radiologically stable. However, the comparatively moderate positive predictive value of PRECISE for predicting histopathological disease progression emphasises the relatively subjective nature of the system, particularly when determining PRECISE category 4 lesions as demonstrating "clinically significant" radiological progression [12].…”
Section: Introductionmentioning
confidence: 99%
“…[24]. In addition, findings of the PRECISE trial revealed that patients without radiological progression during active surveillance have a very low probability of clinical progression [25]. However, the Canary Prostate Active Surveillance Study (PASS) investigators found in a large cohort of men on active surveillance, who subsequently underwent mpMRI-targeted biopsy, that 11% harbored GG 2 PCa within the targeted lesion, while 13% had GG 2 PCa outside of it [26].…”
Section: Implication Of Comprehensive Evaluation For Therapy Decisionmentioning
confidence: 99%